Effect of Management Change, Company Size, and Audit Opinion on Auditor Switching - Rahmadhani Diea Nuraulia (Journal of Islamic Economics and Business, 2023)
This study aims to analyze the influence of management change, company size, and audit opinion on auditor switching. Using dummy variables for management change and audit opinion, and log total assets to measure company size, the research was conducted with purposive sampling, selecting 15 companies from the transportation sub-sector listed on the BEI between 2018 and 2021. Logistic regression was used for data analysis. The results indicate that management change, company size, and audit opinion do not significantly affect auditor switching. The findings offer valuable insights for investors and shareholders, emphasizing the importance of carefully examining financial reports, particularly audit results, to make informed investment decisions. For companies, the study highlights the need for meticulous decision-making when considering auditor switching. Additionally, for auditors, the research underscores the importance of maintaining independence by avoiding overly long-term relationships with clients. Future research could explore other variables and expand the sample size. Nonetheless, this study contributes valuable information to the field of auditor switching and its implications on various stakeholders